Priority criteria for the provision of medical assistance versus protection of human dignity (Ius Novum, 2023)
The article deals with the potential infringement of human dignity through the choice of priority criteria for the provision of medical assistance in an emergency situation, when the treatment can only be provided for one person. The lack of sufficient equipment during the SARS-Cov-2 pandemic is a key example, but examples of acute shortage of medical personnel and various types of equipment are also analysed. The assumption made in the article is that selection guidelines need to be established for medical personnel. The text presents the concept of violation of human dignity and the issue of inability to provide assistance to an adequate number of patients. Then, with the use of the dogmatic-legal method, the proposed patient selection criteria such as age, social position, physical condition, and occurrence of comorbidities are analysed. As a result of the analysis, it is concluded that, due to the protection of human dignity, it is unacceptable to take away the assistance already provided for a patient (disconnection from the apparatus) in order to save the health of another patient. The criterion of assessing the patient’s health condition is unquestionable, whereas the choice of other decisive factors, such as a person’s social standing, may lead to unjustified discrimination and inequality.